Characterization of the complete plastid genome of Cardiocrinum cathayanum, an endemic medicinal plant in China. Issue 1 (2nd January 2019) - Wang, Ning; Bai, Ji-Qing; Dong, Peng-Bin; Zhang, Ting-Ting; Wang, Ruo-Nan; Wang, Jiu-Xia; Liu, Hong-Yan; Liang, Ru-Yun; Tuo, Pei-Pei; Jing, Xiang-Ting; Wang, Xiao-Juan
Abstract: The complete chloroplast genome from Cardiocrinum cathayanum (Liliaceae), an important herbaceous perennial species of the Liliaceae, is determined in this study. We characterized its whole plastid genome sequence using the Illumina sequencing platform. The whole plastid genome of C. cathayanum was a typical quadripartite circular molecule with 152, 502 bp in length, comprised of a large single copy region of 82, 517 bp, a small single copy region of 17, 311 bp, and two inverted repeat regions of 26, 337 bp. A total of 136 genes, 84 protein-coding genes, 38 tRNA, and 8 rRNA genes were identified. The GC content in the chloroplast genome, LSC region, SSC region, and IR region were 42.5, 34.9, 30.8, and 42.5%, respectively. Phylogenetic analysis suggested that C. cathayanum is more closely related with Allium cepa, Allium prattii, Amana edulis, and Erythronium sibiricum, these species were clustered into a clade with high bootstrap support.